New insights into sex differences in primary biliary cholangitis. Gender difference in primary biliary cholangitis - Ying-Hsuen Wu; Yi-Lin Chiu; Jung-Chun Lin; Hsuan-Wei Chen (Journal of the Pakistan Medical Association, 2022)
Objective: To highlight the clinical characteristics of primary biliary cholangitis on the basis of gender in terms of the extent of liver injury and extra-liver autoimmune expressions. Methods: The retrospective study was conducted at the Tri-Service General Hospital, Taiwan, and comprised data of patients aged >20 years diagnosed with primary biliary cholangitis between January 2000 and December 2018. Patients in the control group were randomly selected from the health examination centre. Liver injury manifestations and susceptibilities were analysed along gender lines. The gene expression microarray data from the National Centre for Biotechnology Information Gene Expression Omnibus database was also used to explore the relationship between autoimmune-induced inflammation and androgen response expression. Statistical analysis was done using Graph-Pad Prism 7.0. Results: Of the 75 cases, 63(84%) were females with a mean age of 64.6±1.78 years, and 12(16%%) were males with a mean age of 46.6±5.6 years. Of the 66 controls, 55(83.3%) were females with a mean age of 51.67 years, and 11(16.6%) were males with a mean age of 45.9 years. There were no significant differences in terms of liver profiles related to gender in the control group (p>0.05). Among the cases, male patients showed fewer extrahepatic autoimmune disorders and more severe liver injuries before or after ursodeoxycholic acid treatment (p<0.05). There was a positive correlation between androgen receptor response and the extent of systemic inflammation (p<0.05). Conclusion: The association between androgen receptor responses and inflammation was linked to gender-related hepatic injuries, --Ciontinue